Validity and reliability of external apical root resorption (EARR) measurements: a 3D cone beam computed tomography (CBCT) study - Fazal Shahid,; Shifat A Nowrin,; Norma Ab Rahman,; Saidi Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study was to evaluate the validity and reliability of external apical root resorption (EARR) measurements on commercial and open source software. The data sources were CBCT high volumetric data acquisition from the Malay ethnic group who are undergoing orthodontic treatment in School of Dental Sciences, Universiti Sains Malaysia. A total of 16 CBCT radiograph with 512 variables were measured using the Planmeca Romexis TM Software 2.3.1.R (Helsinki, Finland) and 3D Slicer v. 4.8.1 (open-source software, http://www.slicer.org). Two examiners (A and B) carried out all the measurements of the selected radiographs using the two softwares. Intra class correlation (ICC) coefficient test was applied to check the validity and reliability of EARR measurements. The validity of the 3D EARR measurements from both examiners A and B showed strong correlations. Moreover, ICC co-efficient values of inter examiner A and B were all in the range of strong correlation for EARR measurements in which reliability coefficient values were comparable with the measurements using Planmeca Romexis and 3D Slicer, respectively. All ICC coefficient values were positively correlated. Linear measurements of EARR using 3D CBCT in both commercial and open source software and are valid and reliable.